An investigation on public knowledge towards biomedical waste management - SHREE, MS. K.C. RAJA; MR. PRAVEEN. B (The journal of contemporary issues in business and government, 2020)
Biomedical waste management The effect of hospital waste on health and the environment is important. It can be seen from this research that there is an immediate need to raise alertness, education on medicinal waste issues.To assure health and environmental protection, a proper waste management strategy is required. More information on effects, disposal to specific conclusions is needed to be collected. For developing countries, find options and suitable technology. Need thorough analysis of waste and aspects. Partly because agriculture has become less and less productive. By 2030, 65 percent of the world’s population is projected to be living in cities. Due to low and lack of awareness, the infrastructure needed for this lop-sided growth of the cities is due to waste collection in the unplanned extensions in larger cities. The air quality in the city’s surroundings is so bad that is estimated that about two million children under the age of five die each year from respiratory infections..It is a mystery how the wealthy are callous to the climate, such as doctors and higher officials working in such public places and part of their day time in these places. In fact, hospitals produce a large amount of hazardous waste. In establishing countries such as India,the amount of non liquid waste produced by hospitals has increased rapidly and innovations are implemented.